PS02.045: EXPRESSION AND CLINICAL SIGNIFICANCE OF LEUCINE-RICH REPEAT-CONTAINING PROTEIN 8A (LRRC8A) IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Konishi, Tomoki; Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Kudo, Michihiro; Shoda, Katsutoshi; Kosuga, Toshiyuki; Arita, Tomohiro; Morimura, Ryo; Murayama, Yasutoshi; Kuriu, Yoshiaki; Ikoma, Hisashi; et al.
Abstract: Background: All cells have regulatory volume decrease (RVD) function to maintain cell volume. When the cell volume changes, the anion channels on the cell membrane are activated and keep constant cell volume due to water flow. Leucine-Rich Repeat-Containing protein 8 A (LRRC8A) was first reported in 2014 as the main constituent protein of this anion channel. In normal tissues, LRRC8A is thought to control cell volume regulation and is thought to be involved in cell cycle and death. However, its expression and significance in esophageal squamous cell carcinoma (ESCC) remains unclear. In this study, we examined to investigate the clinicopathological significance of its expression in ESCC and the role of LRRC8A in tumor function. Methods: An immunohistochemical analysis was performed on 64 patients with ESCC who underwent curative surgery in our department. We carried out knockdown using siRNA to evaluate the role of LRRC8A in ESCC cells. Results: LRRC8A was expressed in the cell membrane and cytoplasm of cancer cells. We divided ESCC patients into 2 groups by referring to the staining scores; a high expression group with staining scores ≥ 1.0, n = 53, and a low expression group with staining scores < 1.0, n = 11. In correlation analysis with clinicopathologic factors, high LRRC8A expression tended to have a positive correlation with the presence or absence of lymph node metastasis ( P = 0.059). In the survival analysis, the 5-year overall survival rate of patients with high LRRC8A expression (43.4%) was significantly lower than that of patients with low LRRC8A expression (90.0%) ( P = 0.013). Cox proportional hazard analysis showed that high LRRC8A expression was an independent poor prognostic factor ( P = 0.013, HR = 6.67). LRRC8A was strongly expressed in TE15 and KYSE170 human ESCC cells. The depletion of LRRC8A using siRNA inhibited cell proliferation, migration, invasion and induced apoptosis. Conclusion: The LRRC8A expression is related to worse prognosis in ESCC patients and regulates tumor progression. Nest step, we will carry out further investigation to reveal how to regulate tumor function by microarray analysis. Disclosure: All authors have declared no conflicts of interest.